ANALISIS EFEKTIVITAS SISTEM INFORMASI KEUANGAN DAERAH (SIKD) PEMERINTAH KABUPATEN JEMBRANA - Wartini, Ni Nengah; Yasa, I Gst Wayan Murjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
Financial management of the local government is based on the concept of Value for Money, so that each program and activity implemented by the government need to be evaluated in terms of its effectiveness. The purpose of this study was to analyze the effectiveness of Jembrana government's financial information system, from the dimensions of the quality of system, information, services, management motivation, users’ satisfaction, and benefits of the system for the organization. The study was conducted at 38 SKPD of Jembrana Regency Government The study sample consisted of 114 employees directly involved with financial management. Data were collected using a questionnaire and further analyzed by using descriptive analysis and with the technique Partial Least Square (PLS). The results showed that the effectiveness of the SIKD of the Jembrana Government was effective. Testing the hypothesis using the PLS indicated that the quality of the systems and the information was significant and having a direct impact on the users’ satisfaction and indirectly significantly affect the profit/benefits of the system for the organizations through intervening the users’ satisfaction. The users’ satisfaction and management motivation was significant and had a direct effect on the system benefits for the organization. To improve the effectiveness of information systems, it is necessary to improve the service quality and users’ satisfaction surveys for the information system should be done on a regular basis as an evaluation and input to the development of the system so that the implementation of information systems becomes really efficient, economical, effective and accountable
Keywords: effectiveness, sikd, value for money, accountable